O processo decisório na Constituição de 1988: práticas institucionais - Souza, Márcia Teixeira De [UNESP] (CEDEC, 2003)
The making of the Brazilian Constitution of 1988 is examined along two axis. The first concerns the establishment of a method for discussion and approval of the constitutional text. The second refers to the points of view of the legislators about the institutional relations involving the executive and legislative branches.

Discute-se a elaboração da Constituição de 1988 a partir de dois eixos. O primeiro examina o conjunto das regras que definiu um método de discussão e aprovação do texto constitucional. O segundo destaca as visões dos parlamentares sobre as novas relações institucionais entre o Executivo e o Legislativo.
The decision-making process in the Brazilian Constitution (1988): institutional practices
Keywords: Constitution; Constitution making; decision process; Constituição; elaboração constitucional; processo decisório